Marine or freshwater? Accessing the paleoenvironmental parameters of the Caldas Bed, a key marker bed in the Crato Formation (Araripe Basin, NE Brazil) - Varejão, Filipe Giovanini; Silva, Victor Ribeiro [UNESP]; Assine, Mario Luis [UNESP]; Warren, Lucas Veríssimo [UNESP]; Matos, Suzana Aparecida [UNESP]; Rodrigues, Mariza Gomes [UNESP]; Fürsich, Franz Theodor; Simões, Marcello Guimarães [UNESP] (Sociedade Brasileira de Geologia, 2020)
The Aptian Crato Formation is world renowned for its well-preserved fossils in microbially-induced laminated limestones, which are regarded as one of the main Cretaceous Konservat-Lagerstätte of the geological record. Detailed stratigraphic investigation and mapping of the up to 90-m-thick Crato Formation at the eastern border of the Araripe Plateau allowed recognition of a regionally persistent fossil-bearing muddy interval, herein defined as the Caldas Bed. At its type locality, it is defined as an up to 2-m-thick coarsening-upward succession of grey/green mudstone and interbedded sandy siltstone and claystone. The 0.85- to 2-m-thick interval was recognized in several localities along the outcrop belt, and it is bounded by sharp, lower (Konservat-Lagerstätte limestone) and upper (sandstone and heterolithic facies) contacts. Despite previous literature data suggesting the presence of marine mollusks, the bed contains freshwater bivalves, small gastropods, spinicaudatans, plant remains, trace fossils, and rare ostracods. The Caldas Bed records benthic paleocommunities representing a short-term isochronous regional freshening event, marked by abrupt changes in sedimentation pattern, bathymetry, salinity, oxygenation and water chemistry.
Keywords: freshwater mussels; gastropods; trace fossils; lacustrine deposits; marker bed; Aptian